2016
DOI: 10.1007/s00221-016-4644-2
|View full text |Cite
|
Sign up to set email alerts
|

Deficits in motor abilities for multi-finger force control in hemiparetic stroke survivors

Abstract: The ability to control redundant motor effectors is one of hallmarks in human motor control, and the topic has been studied extensively over several decades since the initial inquiries proposed by Nicholi Bernstein. However, our understanding of the influence of stroke on the control of redundant motor systems is very limited. This study aimed to investigate the effect of stroke-related constraints on multi-finger force control abilities in a visuomotor task. Impaired (IH) and less-impaired hands (LH) of 19 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 54 publications
1
11
0
Order By: Relevance
“…Either way, high variability of muscle synergies warrants further exploration, especially when applying synergy analyses to individuals with brain injury, because such variability across repetitions of the same movement could be interpreted as a challenge to the synergy hypothesis which postulates that synergies represent a fixed modular pattern of motor activities in purposeful behavior ( Ivanenko et al, 2006 ; Bizzi and Cheung, 2013 ). Increased motor variability across trials is often observed in patients with brain injuries ( Kim et al, 2016 ) or older adults ( Lovden et al, 2007 ). Moreover, muscle activity patterns can vary owing to changes in sensory input and subcortical reflexes ( Sinkjaer et al, 2000 ; Kim et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Either way, high variability of muscle synergies warrants further exploration, especially when applying synergy analyses to individuals with brain injury, because such variability across repetitions of the same movement could be interpreted as a challenge to the synergy hypothesis which postulates that synergies represent a fixed modular pattern of motor activities in purposeful behavior ( Ivanenko et al, 2006 ; Bizzi and Cheung, 2013 ). Increased motor variability across trials is often observed in patients with brain injuries ( Kim et al, 2016 ) or older adults ( Lovden et al, 2007 ). Moreover, muscle activity patterns can vary owing to changes in sensory input and subcortical reflexes ( Sinkjaer et al, 2000 ; Kim et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…Despite extensive research on the association between strength and motor function in stroke survivors, the evidence regarding role of impaired motor control on functional capacity is sparse, especially for the lower-limb (13, 14). A study on the upper-limb motor control demonstrated that increased variability and reduced accuracy for finger forces was related to poor functional outcome during grasp and release in stroke (15). The influence of strength and motor control on functional capacity potentially varies with the severity of stroke motor impairments.…”
Section: Introductionmentioning
confidence: 99%
“…In previous stroke studies, coordination patterns during voluntary movements were not consistent, reporting unchanged IC [18,40], decreased IC [41], and increased IC [20], along with unchanged TIV [18,40], and greater TIV [19,20]. However, TRV was found to be greater than in control [19,20,41]. The previous studies suggested that this unexpected finding might have resulted from large inherent variability of neural signals between motor cortex and effectors [42] or being more dependency of effectors in the patients with stroke [43].…”
Section: Index Of Coordinationmentioning
confidence: 75%
“…In a person with neurological diseases such as Parkinson's disease [14], olivoponto-cerebellar atrophy [15], multiple sclerosis [16] and spinocerebellar degeneration [17], different patterns of motor synergies have been observed often with decreased TIV and increased TRV as compared to healthy groups. However, previous stroke studies have reported inconsistent results on TRV and TIV between stroke group and healthy group during a UE reaching task [18][19][20]. One of the possibilities for the inconsistent results may be attributed to changes in passive properties of UE after stroke.…”
Section: Introductionmentioning
confidence: 94%